Analisis Lingkungan Air Limbah Produksi Kerupuk Ikan pada Parameter Fisika, Kimia, Mikrobiologi: Environmental Assessment of Fish Cracker Production Wastewater on Physical, Chemical, and Microbiological Parameters - Mudzakaroh, Luluk; Syauqi , Ahmad; Prasetyo, Hamdani Dwi (Jurnal SAINS ALAMI (Known Nature), 2026)
The food industry sector, particularly fish cracker production, contributes significantly to the economy; however, it also has the potential to pollute the environment through wastewater containing high levels of organic matter. If discharged without proper treatment, this waste can degrade water quality, reduce dissolved oxygen (DO) levels, generate unpleasant odors, and cause the death of aquatic biota. This study aimed to determine the level of water pollution using the Pollution Index method in irrigation rivers surrounding the fish cracker production unit UD. X. The method used was a comparative quantitative descriptive survey with grab sampling conducted at three stations: upstream, wastewater outlet, and downstream. The analyzed parameters included physical parameters (temperature, TDS, odor, and color), chemical parameters (pH, DO, and BOD), and microbiological parameters using the plate count method. The results showed that the pollution index values in the upstream section ranged from 4.1–5.1, which falls into the lightly to moderately polluted category. At the wastewater outlet, the pollution index values ranged from 2.5–4.4, while the downstream section ranged from 2.5–3.7; both were classified as lightly polluted. The water quality status indicated that the upstream section was categorized as lightly to moderately polluted, whereas the wastewater outlet and downstream sections were categorized as lightly polluted. A positive correlation was found between organic load (BOD) and microorganism abundance, where the highest abundance value of 1.78 × 10⁷ CFU/mL was identified at locations with higher BOD levels. Self-purification occurred in the area before the wastewater outlet due to the presence of a small dam that slowed water flow, increased oxygen input, and enhanced the degradation of organic matter. Keywords: river water, wastewater, pollution index, fish crackers ABSTRAK Sektor industri makanan, khususnya produksi kerupuk ikan, berkontribusi signifikan terhadap perekonomian, namun berpotensi mencemari lingkungan melalui limbah cair dengan kandungan bahan organik tinggi. Limbah dapat menurunkan kualitas perairan apabila dibuang tanpa pengolahan, penurunan oksigen terlarut (DO), timbulnya bau, serta kematian biota akuatik. Penelitian ini bertujuan untuk menentukan tingkat pencemaran air menggunakan metode Indeks Pencemaran (IP) pada sungai irigasi di sekitar unit produksi kerupuk ikan UD. X. Metode yang digunakan adalah survei deskriptif kuantitatif komparatif dengan pengambilan sampel secara grab sampling pada tiga stasiun, yaitu hulu, outlet limbah, dan hilir. Parameter yang dianalisis meliputi fisika; suhu, TDS, bau, warna, kimia; pH, DO, BOD, dan mikrobiologi dengan metode lempeng. Hasil penelitian menunjukkan, nilai indeks pencemaran pada bagian hulu berkisar 4,1–5,1 yang termasuk dalam kategori tercemar ringan hingga sedang. Pada outlet limbah, nilai indeks pencemaran berkisar 2,5–4,4, pada bagian hilir berkisar 2,5–3,7, keduanya termasuk dalam kategori tercemar ringan. Status mutu air menunjukkan bahwa bagian hulu berada pada kategori tercemar ringan hingga sedang, sedangkan outlet limbah dan hilir termasuk dalam kategori tercemar ringan. Terdapat korelasi positif antara beban organik (BOD) dengan kelimpahan mikroorganisme, di mana nilai kelimpahan tertinggi mencapai 1,78 × 10⁷ CFU/mL ditemukan pada lokasi dengan BOD yang lebih tinggi. Self-purification terjadi pada lokasi sebelum outlet limbah dengan adanya dam kecil yang memperlambat aliran, masuknya oksigen, dan meningkatkan degradasi bahan organik. Kata kunci: air sungai, air limbah, indeks pencemaran, kerupuk ikan